PENGARUH MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES TERHADAP HASIL BELAJAR IPAS PADA MATERI WUJUD BENDA DIKELAS IV SDN 128 PALEMBANG - Maulani, Meva; Rizhardi, Rury; Hermansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low learning outcomes of students in the IPAS subject on the material of the states of matter in grade IV at SD Negeri 128 Palembang. This is caused because the learning process still uses conventional methods, making students less active and less able to understand the material delivered by the teacher. This study aims to determine the effect of the Examples Non Examples learning model on IPAS learning outcomes for the material of the states of matter in grade IV at SD Negeri 128 Palembang. The research sample consisted of all fourth-grade students, comprising two classes, using a total sampling technique, with class IV.A as the experimental class and class IV.B as the control class at SD Negeri 128 Palembang. This study uses an experimental research method with a Pre-test Post-test Control Group Design. Data collection techniques were conducted through tests and documentation. Student learning outcomes data were obtained through multiple-choice tests. The data analysis method uses quantitative analysis with normality tests, homogeneity tests, and hypothesis testing using the t-test. The results of the Independent Sample T-Test calculation show a t_calculated value of 3.922 with a significance value (Sig. 2-tailed) of 0.000. Because the significance value 0.000 < 0.05, Ha is accepted and Ho is rejected. Based on the research results obtained, it shows that there is an effect of the non-example example learning model on IPAS learning outcomes in the matter of different shapes in grade IV at SDN 128 Palembang.